Human Application of Ex Vivo Expanded Umbilical Cord-Derived Mesenchymal Stem Cells: Enhance Hematopoiesis after Cord Blood Transplantation. Issue 11 (November 2013) - Wu, Kang-Hsi; Tsai, Chris; Wu, Han-Ping; Sieber, Martin; Peng, Ching-Tien; Chao, Yu-Hua
Delayed hematopoietic reconstitution after cord blood (CB) transplantation (CBT) needs to be overcome. Bone marrow-derived mesenchymal stem cells (BMMSCs) have been found to enhance engraftment after hematopoietic stem cell transplantation. However, getting BMMSCs involves an invasive procedure. In this study, umbilical cord-derived mesenchymal stem cells (UCMSCs) were isolated from Wharton's jelly and cryopreserved in the UCMSCs bank. Compared with BMMSCs, we found that UCMSCs had superior proliferative potential. We found that NOD/SCID mice cotransplanted with CB and UCMSCs demonstrated significant human CD45 + cell engraftment compared with those transplanted with CB alone. Then, 20 patients with high-risk leukemia were prospectively randomized to either receive cotransplantation of CB and ex vivo expanded banked UCMSCs or to receive CBT alone. No serious adverse events were observed in the patients receiving UCMSC infusion. The time to undergo neutrophil engraftment and platelet engraftment was significantly shorter in the eight patients receiving cotransplantation than that in the 12 patients receiving CBT alone ( p = 0.003 and p = 0.004, respectively). Thus, application of ex vivo expanded banked UCMSCs in humans appears to be feasible and safe. UCMSCs can enhance engraftment after CBT, but further studies are warranted.